MUSLIM TIONGHOA SEBAGAI LIYAN DALAM KONSEP UKHUWWAH ISLAMIYAH - Ade Irma (Jurnal Dakwah Tabligh, 2017)
Tionghoanesse moeslem is part of Tionghoa’s ethnic, but instead of known as a Tionghoa, they do not know as a part of moeslem community. During the Orde Baru era, the Tionghoa’s having a repression from government. Back than they were forced to be ‘Indonesian’ with various total assimilation programs. While Tionghoa’s ethnic become minority and was being repressed, the Tionghoanesse moeslem community was being more repressed. As we know, the Tionghoa’s moeslem community is a minor people on minority group, so they are having a double difficulty to face Indonesia’s social and cultural costum.            During the reformation era, government withdrawing the rules that suffers them, in this era Tionghoa’s ethnic having their own freedom to express them self and having their own Tionghoa’s identity. PITI Surabaya, as an organization which collecting Tionghoa’s moeslem community in Surabaya, has various ways to break the stigma about Tionghoa’s moeslem community. Although, PITI Surabaya has tried various ways to show their exsistence but, the discrimination on them are still on the way until today.            The focus on this paper is how PITI Surabaya with all their various ways in reducing discrimination can survive the contestation on their identity’s construction and discrimination among other moeslem’s community in Surabaya.